2017
DOI: 10.1002/jbm.a.35978
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in the aseptic loosening of total joint replacements

Abstract: Peri-prosthetic osteolysis remains as the main long-term complication of total joint replacement surgery. Research over four decades has established implant wear as the main culprit for chronic inflammation in the peri-implant tissues and macrophages as the key cells mediating the host reaction to implant-derived wear particles. Wear debris activated macrophages secrete inflammatory mediators that stimulate bone resorbing osteoclasts; thus bone loss in the peri-implant tissues is increased. However, the balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 139 publications
(352 reference statements)
0
59
0
Order By: Relevance
“…This adds weight to the clinical relevance of many studies investigating the osteogenic and inflammationinducing potential of osteoblastic cells following Co exposure in vitro and the derived implication on its direct involvement in the pathomechanism of osteolysis. [46][47][48] Furthermore, it must be considered that not only Co and Cr account for the overall metal exposure in peri-implant BM. Particularly in the adjacent BM of stemmed prostheses and multicomponent revision implants, large quantities of particles consisting of Ti, Ta, and Zr were detected both intracellularly and extracellularly in the micron-, submicron-and nanorange.…”
Section: Discussionmentioning
confidence: 99%
“…This adds weight to the clinical relevance of many studies investigating the osteogenic and inflammationinducing potential of osteoblastic cells following Co exposure in vitro and the derived implication on its direct involvement in the pathomechanism of osteolysis. [46][47][48] Furthermore, it must be considered that not only Co and Cr account for the overall metal exposure in peri-implant BM. Particularly in the adjacent BM of stemmed prostheses and multicomponent revision implants, large quantities of particles consisting of Ti, Ta, and Zr were detected both intracellularly and extracellularly in the micron-, submicron-and nanorange.…”
Section: Discussionmentioning
confidence: 99%
“…The biotoxicity, biocompatibility and mechanics properties had been greatly renovated with the regeneration of prosthesis materials, but the aseptic loosening caused by wear particles still remain unsolved [1]. Upon activation by wear particles, macrophages release a series of proinflammatory cytokine like TNF-α, IL-6 and IL-1β which induce the recruitment of macrophage and trigger the activation of osteoclast precursors [4,5]. It's been reported that the interaction between TNF-α and RANKL promotes osteoclast activity associated with wear debris [14].…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte/macrophage lineage cells play a significant role in immunology, tissue homeostasis, disease pathogenesis and inflammation. Macrophages are the key players in the response to wear particles from prosthesis [5]. Macrophages, upon activation by wear particles, release a series of proinflammatory cytokine such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) which recruit and activate osteoclast precursors and trigger inflammatory bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…In arthroplasty and bone tissue engineering, in vitro testing of the interactions between MSC and diverse orthopaedic biomaterials represents an obligatory step [8][9][10]. All biomechanical, biochemical and biological approaches that enhance bone integration and provide MSC with good functional capacity are a step forward in the endeavours to achieve life-long prosthetic replacement [11]. To this end, there is a need for an effective in vitro model for studying MSC functions at implant-tissue interface.…”
Section: Introductionmentioning
confidence: 99%